Application of a Novel 68Ga-HER2 Affibody PET/CT Imaging in Breast Cancer Patients - Miao, Haitao; Sun, Yuyun; Jin, Yizi; Hu, Xichun; Song, Shaoli; Zhang, Jian (Frontiers in Oncology, 2022)
Background: Breast cancer is a heterogeneous disease, and the human epidermal growth factor receptor 2 (HER2) expression may vary considerably between primary and metastatic lesions, or even within a single lesion. Repeated biopsies cannot always be performed. In this feasibility trial, we assessed whether a novel 68Ga-NOTA-MAL-MZHER2 (68Ga-HER2) affibody PET/CT could determine HER2 status when there was clinical need to know about HER2 status of each lesion. Methods: 68Ga-HER2 affibody PET/CT was performed in breast cancer patients if HER2 status remained unclear after standard examinations (including bone scan, 18F-FDG PET/CT, CT, and feasible biopsy). All available images for each patient were evaluated through an independent review of two committee-certified radiologists with nuclear medicine expertise. In case of discrepancy, adjudication by a third radiologist was performed as needed. All radiologists were blinded to the clinical information. Results: Twenty-four patients were enrolled. 68Ga-HER2 affibody PET/CT was requested by physicians due to the following reasons: 6 with multiple primary cancers, 13 with metastases not amenable to biopsy or repeated biopsy, 6 with inconsistent HER2 status between primary and metastatic lesions, 4 with different HER2 status within different metastases. Final PET report demonstrated that the 68Ga-HER2 affibody tumor uptake was considered positive in 16 patients, negative in 7 patients, and equivocal in one patient. The heterogeneity of 68Ga-HER2 affibody uptake was observed, with a maximal 8.5-fold difference within one patient and a maximal 11-fold difference between patients. 68Ga-HER2 affibody PET/CT demonstrated a high diagnostic accuracy in differentiating HER2-enriched breast cancer, with a sensitivity of 91.7% and a specificity of 84.6%, regardless of prior lines of anti-HER2 therapies. Conclusion: 68Ga-HER2 affibody PET/CT imaging could provide valuable information on HER2 expression of each tumor in the body of patients, which may help in personalized clinical decision making. Its value is now under systemic assessment.